2021
DOI: 10.2987/21-6995.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Culex coronator in the USA

Abstract: In 1920, Culex coronator was reported from San Benito, Texas, and later in Arizona, New Mexico, and Oklahoma. In 2005, this species was reported to be spreading across the southeastern USA. Now reported in 14 states, it has been found as far north as northern Oklahoma; Memphis, TN; and Suffolk, VA. The public health significance of Cx. coronator is not firmly established, even though it has been implicated as a potential vector of several arboviral diseases. This study aims to document additional Cx. coronator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Mosquito species in this genus are known to be vectors of medical and veterinary relevance. Pathogens such as WNV, St. Louis virus (SLV), ZIK [89][90][91], and VEE [92] have been found in wild specimens. For example, Baak-Baak et al [93] [96][97][98], that infect humans, birds, primates and other wild vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito species in this genus are known to be vectors of medical and veterinary relevance. Pathogens such as WNV, St. Louis virus (SLV), ZIK [89][90][91], and VEE [92] have been found in wild specimens. For example, Baak-Baak et al [93] [96][97][98], that infect humans, birds, primates and other wild vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Culex Flavivirus (Miranda et al 2019) Ilheus virus (unpublished data reported in Turell et al 2005) St Louis encephalitis virus (Aitken et al 1964;Turell et al 2005) Venezuelan equine encephalitis virus (Burguete et al 1973) West Nile virus (Mackay 2007;Kelly et al 2008;Unlu et al 2010) Zika virus (Elizondo-Quiroga et al 2018) DISTRIBUTION NOTES (Bram 1967;Sames et al 2021) Culex coronator is native to Argentina, Belize, Bolivia, Brazil, Colombia, Costa Rica, Chile, Ecuador, El Salvador, Guatemala, Guyana, Honduras, Mexico, Nicaragua, Panama, Paraguay, Peru, Suriname, United States, Uruguay, and Venezuela (Figure 7). Between the 1920s and 1970s, Culex coronator was reported from several states in the western and central United States (Arizona, New Mexico, Louisiana, Mississippi, Oklahoma, and Texas).…”
Section: Associated Pathogensmentioning
confidence: 99%
“…Between the 1920s and 1970s, Culex coronator was reported from several states in the western and central United States (Arizona, New Mexico, Louisiana, Mississippi, Oklahoma, and Texas). In the early 2000s, the species expanded its United States distribution eastward, and in 2000s and 2010s, it was reported for the first time as far east as Florida and Virginia (Sames et al 2021).…”
Section: Associated Pathogensmentioning
confidence: 99%